2021
DOI: 10.24926/jcotr.v28i1.3540
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Bridge

Abstract: This qualitative study examines the experiences of seven students who were selected to attend a summer bridge program (SBP) located in the U.S. Midwest. Utilizing semi-structured interviews and organizational socialization theory, the study illuminates students’ preconceived notions about what it means to be in an SBP, experiences while in the program, and how those experiences help facilitate a successful transition into the first year of college and beyond. Findings revealed that participating in the SBP pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The Assessment of the ISBA showed 100% of students agreed that the activities and workshops in ISBA of 2022 were relevant and beneficial for their academic and personal development. This confirms what Turner, McCallum, and Benson (2021) say about how "social interactions with faculty, peers, peer-advisors and advisors influenced [students] college experience" (p. 7).…”
Section: Discussionsupporting
confidence: 76%
“…The Assessment of the ISBA showed 100% of students agreed that the activities and workshops in ISBA of 2022 were relevant and beneficial for their academic and personal development. This confirms what Turner, McCallum, and Benson (2021) say about how "social interactions with faculty, peers, peer-advisors and advisors influenced [students] college experience" (p. 7).…”
Section: Discussionsupporting
confidence: 76%
“…It was noted in one paper, which focused on a small number of student experiences (six students) [58], that students had increased motivation as a result of bridge program participation. A similar study [59] found that participants valued the ability to experience college work and to enter college in a safe, welcoming environment, thereby increasing their self-confidence and self-esteem. In light of this value of the program, some bridge programs specifically focused on promoting this sense of belonging, e.g., [60].…”
Section: Impact Of Programsmentioning
confidence: 80%